On the Optimality of Pure Strategies - Wagner, Harvey M. (Management Science, 1960)
In Manne [Manne, A. S. 1960. Linear programming and sequential decisions. Management Sci. (April).] has suggested a linear programming formulation for on optimal steady state solution of sequential decision models. In this note we offer a proof which appeals primarily to the properties of linear programs that an optimal solution exists involving only pure strategies.